Peran Guru PAI dalam Menanamkan Sikap Kepedulian Siswa Terhadap Kebersihan Sekolah di SMAN 1 Gondang Wetan - Mukarromah, Dewi Aissatul (Tarbiyatuna Kajian Pendidikan Islam, 2026)
School cleanliness is crucial for fostering a healthy learning environment, yet many students lack concern for environmental hygiene. This study aims to examine the role of Islamic Education (PAI) teachers in instilling students’ awareness of cleanliness at SMAN 1 Gondang Wetan and to identify supporting and inhibiting factors. Employing a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation involving PAI teachers, students, and school stakeholders. Findings reveal that PAI teachers serve as educators, guides, role models, and motivators, integrating Islamic teachings on cleanliness through classroom learning, habituation, and exemplary behavior. Programs such as the Friday Clean Movement, classroom cleanliness competitions, and waste banks support these efforts. Supporting factors include school support and the structured Adiwiyata program, while inhibiting factors encompass limited facilities, lack of student awareness, and minimal parental involvement. This study underscores the need for synergy among schools, families, and communities to enhance the effectiveness of fostering environmentally responsible character.